Aktivitas antikanker ekstrak etanol, fraksi n-heksan, dan etil asetat daun tin (Ficus carica l.) pada sel kanker payudara MCF-7 - Aji Winanta; Widhi Yana Sari (Universitas Islam Indonesia, 2023)
Abstract Background: Breast cancer is ranked as the second-highest cause of death in Indonesia. Many of the available cancer treatments result in severe adverse effects for patients. Tin (Ficus carica L.) leaves contain ingredients that can function as anticancer agents. Objective: The study aims to identify phytochemical secondary metabolites in tin leaves and the cytotoxic activity of the extract and tin leaf fraction on MCF-7 cells.Method: Tin leaf powder was macerated with 70% ethanol for 7 days. The extracts were fractionated using n-hexane and ethyl acetate. An identification test with ethanol extract was then carried out using spray reagents. The cytotoxic activity of ethanolic extract, n-hexane and ethyl acetate fraction of tin leaf was determined using the MTT method.Result: The results of the identification with TLC found that the ethanol extract of tin leaves contains flavonoids and steroids. The ethyl acetate fraction of tin leaf was thought to have weak cytotoxic properties with an IC50 value of 274.5877 ug/mL while the ethanol extract and n-heksan fraction of tin leaf do not have cytotoxic properties because they have an IC50 value of 562.827 and 576.3552 ug/mL. Conclusion: Based on the results, tin leaves have the potency to be developed as a chemopreventive agent for MCF-7 breast cancer cells.Keywords: Breast Cancer, MCF-7 cells, tin leaf (Ficus carica), cytotoxic activity